Les exigences de l'impartialité quasi-judiciaire - Garant, Patrice (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1977)
The Supreme Court decision commented upon is another important administrative law decision which relates to principles of natural justice, and especially to the nemo judex rule (freedom from bias). Speaking for the majority, Mr. Justice Laskin states that the function exercised by the National Energy Board under section 44 of the National Energy Board Act is quasi-judicial although it consists in issuing a licence according to an extensive discretionary power. Consequently, principles of natural justice must be applied. The nemo judex rule means that if there is a "reasonable apprehension of bias" due to the past behavior or actions of a member of a quasi-judicial tribunal, that member must be disqualified from acting. Otherwise, the decision rendered by the tribunal must be quashed. Two years before his appointment to the Board, the chairman of the National Energy Board had in fact participated actively in operations and decisions bearing on the very subject-matter subsequently submitted to the Board. That placed the chairman in a situation of conflict of interest, although he had no personal pecuniary interest in the matter involved. The majority of the Supreme Court dissagrees with Mr. Justice de Grandpré's dissent as well as with the decision of the Federal Court of Appeal. Each expresses a point of view which is worth reading. The majority of the Supreme Court applies to administrative boards or tribunals exercising quasi-judicial functions the same critérium as the one applied under the common law to any inferior court. Another remarkable judgment of our Supreme Court.